Fire protection of wooden building structures - Sirko, Z.; Tsapko, O.; Torchilevsky, D.; Tsapko, Yu.; Bondarenko, O.; Apanasenko , V. (Ways to Improve Construction Efficiency, 2023)
The paper covers the issues of fire protection of cellulose-containing materials, in particular wood. It is shown that despite a number of valuable properties that wood possesses, it is a rather flammable material by its composition. It is known from the literature that one of the most important steps in protecting wood from fire is fire protection treatment. It is carried out in two main ways: surface treatment (applying special compounds to the wood surface to form a fireproof layer) and deep impregnation of wood with flame retardants. For the fire protection of OSB samples, a water-based intumescent paint consisting of a system of flame retardants in combination with fillers, pigment, and functional additives was developed. The research was conducted using analytical and experimental methods, which consist of analyzing and studying the provisions of national standards that describe the method for determining the flammability group of substances and materials and the method for determining the fire protection efficiency of fire retardants. The experimental part of the study involved the manufacture of test samples, application of fire retardants to them, recording the temperature of gaseous combustion products, the maximum temperature increase, the time interval for reaching the maximum temperature, the weight of the samples, and the weight loss of the samples. The research methodology states that the wood samples were tested in accordance with DSTU 8829 at the OTM installation. It also provides means for measuring the flue gas temperature, test time, and determining the mass loss of samples before and after testing. The test results showed that the developed fire retardant based on intumescent paint provides a group of refractory materials in accordance with DSTU 8829, i.e., the wood protected by this method belongs to refractory materials, namely: the flue gas temperature does not exceed 260˚C, the mass loss of samples after testing is not more than 60%.